Penerapan Laporan Keuangan Entitas Berorientasi Nonlaba Berdasarkan ISAK 35: (Studi Kasus Pada Panti Asuhan Kasih Murni Tahun 2021) - Sahala Purba; Andro Siregar; Rasdianta Purba; Melva Esnida Saragih; Vivi Valensia br Karo; Purnama Sari Sinulingga; Emiya Brahmana (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
This journal discusses the presentation of financial statements on non-profit entities. Initially, non-profit entities presented financial statements based on PSAK 45 which was later changed to ISAK 35. One of the non-profit entities included in the church, the most important aspect of which was financial accountability. Good accountability is obtained from generally accepted accounting standards. The purpose of this journal is to find out the presentation of financial statements based on the implementation of ISAK 35 which began on January 1, 2020. The object of this paper is the presentation of the financial statements of the Orphanage Kasih Murni. The data were collected through a series of interviews and observations. The financial statements that will be produced are statements of financial position, statements of comprehensive.